Dispersing powders in liquids - Nelson, Ralph D., 1938- (Handbook of powder technology ;, 1988)
This book provides powder technologists with laboratory procedures for selecting dispersing agents and preparing stable dispersions that can then be used in particle size characterization instruments. Its broader goal is to introduce industrial chemists and engineers to the phenomena, terminology, physical principles, and chemical considerations involved in preparing and handling dispersions on a commercial scale. The book introduces novices to: - industrial problems due to improper degree of dispersion; - the nomenclature used in describing particles; - the basic physical phenomena, equations, and chemistry involved in particle interactions; - the analytical techniques used for evaluating solid-liquid interfaces - textbooks, courses, societies, and vendors that can provide an advanced understanding of dispersion phenomena. The book provides resources for more experienced technologists by: - discussing characteristics and applications of the various chemical classes of surfactants; - providing procedures for selecting and optimizing a dispersant for a specific solid-liquid system and end-use constraints; - naming typical commercial surfactants and listing the addresses and telephone numbers of their manufacturers; - illustrating the many physical and chemical equilibria that must be considered in modelling a dispersion and guiding the reader to the sources of both data and advanced theoretical treatments required to implement such models. The author has for several years been a consultant in the field of slurry technology, obtaining information, materials, equipment, and expert advice required to solve slurry problems. He also teaches slurry technology and powder dispersion courses to students who are either engineers recently graduated from college or managers recently transferred to plants that handle slurries. His expertise gives the book a wide appeal: as virtually every manufacturing process involves dispersions of powders in liquids, it is of interest to chemists and chemical engineers in industry; the concise definitions, descriptions and examples make it an ideal reference text for teachers and students.